Notes on Non-Generic Isomonodromy Deformations - Guzzetti, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2018)
Some of the main results of [Cotti G., Dubrovin B., Guzzetti D., Duke Math. J., to appear, arXiv:1706.04808], concerning non-generic isomonodromy deformations of a certain linear differential system with irregular singularity and coalescing eigenvalues, are reviewed from the point of view of Pfaffian systems, making a distinction between weak and strong isomonodromic deformations. Such a distinction has a counterpart in the case of Fuchsian systems, which are well known as Schlesinger and non-Schlesinger deformations, reviewed in Appendix A.